Quality improvement in cardiovascular surgery: results of a surgical quality improvement programme using a nationwide clinical database and database-driven site visits in Japan. Issue 7 (20th November 2019) - Yamamoto, Hiroyuki; Miyata, Hiroaki; Tanemoto, Kazuo; Saiki, Yoshikatsu; Yokoyama, Hitoshi; Fukuchi, Eriko; Motomura, Noboru; Ueda, Yuichi; Takamoto, Shinichi
Abstract : Background: In 2015, an academic-led surgical quality improvement (QI) programme was initiated in Japan to use database information entered from 2013 to 2014 to identify institutions needing improvement, to which cardiovascular surgery experts were sent for site visits. Here, posthoc analyses were used to estimate the effectiveness of the QI programme in reducing surgical mortality (30-day and in-hospital mortality). Methods: Patients were selected from the Japan Cardiovascular Surgery Database, which includes almost all cardiovascular surgeries in Japan, if they underwent isolated coronary artery bypass graft (CABG), valve or thoracic aortic surgery from 2013 to 2016. Difference-in-difference methods based on a generalised estimating equation logistic regression model were used for pre-post comparison after adjustment for patient-level expected surgical mortality. Results: In total, 238 778 patients (10 172 deaths) from 590 hospitals, including 3556 patients seen at 10 hospitals with site visits, were included from January 2013 to December 2016. Preprogramme, the crude surgical mortality for site visit and non-site visit institutions was 9.0% and 2.7%, respectively, for CABG surgery, 10.7% and 4.0%, respectively, for valve surgery and 20.7% and 7.5%, respectively, for aortic surgery. Postprogramme, moderate improvement was observed at site visit hospitals (3.6%, 9.6% and 18.8%, respectively). A difference-in-difference estimator showed significant improvement in CABG (0.29 (95% CI 0.15 to 0.54), p<0.001) and valve surgery (0.74 (0.55 to 1.00); p=0.047). Improvement was observed within 1 year for CABG surgery but was delayed for valve and aortic surgery. During the programme, institutions did not refrain from surgery. Conclusions: Combining traditional site visits with modern database methodologies effectively improved surgical mortality in Japan. These universal methods could be applied via a similar approach to contribute to achieving QI in surgery for many other procedures worldwide.